PENGARUH KEPEMILIKAN, KEPUTUSAN INVESTASI, PENGALAMAN DAN KINERJA FINANSIAL - FRANSISKA SOEJONO (Jurnal Bisnis dan Akuntansi, 2010)
This research is purposed to test the difference in performance between state-owned firms and private-owned firms on 811 firm-year observations in BEI between 1999-2007 period. Multiple comparisons is used to test the hypothesis that state-owned firms have better performance than private-owned firms. Besides that, this research are purposed to test the influence of investment decision and experience to firm’s performance, using ancova model. The result shows that different type of ownership give different effect to firm’s performance. Contrary with the hypothesis, the result shows that state-owned firms have a better performance than private-owned firms. The result also shows that investment decisions and experiences have no significant effect of firm’s performance. This research using control variabel that are year and type of industry.